2020
DOI: 10.1016/j.jclepro.2019.118588
|View full text |Cite
|
Sign up to set email alerts
|

Which is the relationship between the product’s environmental criteria and the product demand? Evidence from the French food sector

Abstract: The purpose of this paper is to identify which environmental criteria can influence the product demand in a context of business-to-business. These criteria can be related to the product's environmental characteristics, to the organization strategies or green practices developed by the firms and to the supplier selection process. Building the conceptual framework from the literature review, a set of environmental criteria were extracted, selected and validated. These criteria were used as a basis for the defini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 63 publications
1
5
0
Order By: Relevance
“…We found a statistically positive direct effect of corporate environmentalism on product quality (C I PQ = 0.87; p < 0.05). In line with our results, Palacios-Argüello and others [37] confirm that organic labelled raw materials incorporated in the production process and products placed at close proximity to the stakeholders, would improve product quality. They also found that environmental product quality leads to product demand especially when product quality is an indispensable criterion when choosing business partners and suppliers.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We found a statistically positive direct effect of corporate environmentalism on product quality (C I PQ = 0.87; p < 0.05). In line with our results, Palacios-Argüello and others [37] confirm that organic labelled raw materials incorporated in the production process and products placed at close proximity to the stakeholders, would improve product quality. They also found that environmental product quality leads to product demand especially when product quality is an indispensable criterion when choosing business partners and suppliers.…”
Section: Discussionsupporting
confidence: 92%
“…Recent studies show that green strategy holds various advantages for the firm [36][37][38], and relates positively to environmental performance [3,15]. Majid et al [36], Fores [39], and Li et al [40] argued that firms will experience an increase in environmental performance when environmental business strategies are developed in line with pollution prevention, regulation compliance, materials recycling, and waste reduction.…”
Section: Green Strategy and Environmental Performancementioning
confidence: 99%
“…In addition, the exhaust fumes from industrial waste and vehicles (aircraft, trucks) related to the food system contribute expressively to air pollution [79]. Air pollution not only reduces the supply of raw ingredients but can affect consumer demand and choice [80], and food supply will eventually change food prices [81].…”
Section: Discussionmentioning
confidence: 99%
“…Retail product management also requires attention to the demand for these items to mitigate financial and environmental problems resulting from reduction in sales (Buisman et al, 2019;Lu et al, 2020). Analysis of this scenario suggests that product management can reduce FW and also expand retailer's earnings (Palacios-Argüello et al, 2020). The literature also presents alternatives for the destination of products near the end of validity that retailers were unable to sell .…”
Section: Productmentioning
confidence: 99%